2021
DOI: 10.1101/gad.345579.120
|View full text |Cite
|
Sign up to set email alerts
|

Protein-bound molybdenum cofactor is bioavailable and rescues molybdenum cofactor-deficient C. elegans

Abstract: The molybdenum cofactor (Moco) is a 520-Da prosthetic group that is synthesized in all domains of life. In animals, four oxidases (among them sulfite oxidase) use Moco as a prosthetic group. Moco is essential in animals; humans with mutations in genes that encode Moco biosynthetic enzymes display lethal neurological and developmental defects. Moco supplementation seems a logical therapy; however, the instability of Moco has precluded biochemical and cell biological studies of Moco transport and bioavailability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…This work demonstrated that protein-bound Moco is both stable and bioavailable to C. elegans and provides a therapeutically relevant demonstration of previous observations that Moco from plant, animal, or bacterial sources can be used interchangeably and that Moco is stabilized when bound to protein (Schwarz 2005). Just as E. coli-derived cPMP was successfully used by both mice and humans in supplementation tests (Schwarz et al 2004;Veldman et al 2010;Schwahn et al 2015), Warnhoff et al (2021) demonstrated that C. elegans can use protein-bound Moco from a spectrum of exogenous origins. These findings raise a delightful possibility that proteinbound Moco from diverse sources may serve as an effective supplement for all types of MoCD patients.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…This work demonstrated that protein-bound Moco is both stable and bioavailable to C. elegans and provides a therapeutically relevant demonstration of previous observations that Moco from plant, animal, or bacterial sources can be used interchangeably and that Moco is stabilized when bound to protein (Schwarz 2005). Just as E. coli-derived cPMP was successfully used by both mice and humans in supplementation tests (Schwarz et al 2004;Veldman et al 2010;Schwahn et al 2015), Warnhoff et al (2021) demonstrated that C. elegans can use protein-bound Moco from a spectrum of exogenous origins. These findings raise a delightful possibility that proteinbound Moco from diverse sources may serve as an effective supplement for all types of MoCD patients.…”
supporting
confidence: 53%
“…While the conceptual advances of the studies are commonly found in the connections of metabolic events to animal development, behavior, and aging, some research results have more direct medical relevance. The study on molybdenum cofactor deficiency in this issue of Genes & Development Warnhoff et al (2021) presents an excellent example of using C. elegans as a unique and effective system to study the problem of nutrient deficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1974, I started studying Moco, and in 2021, I retired from my administrative and teaching duties, and I continue conducting Moco research. In collaboration with the young professor Kurt Warnhoff (USA), we study the unique case of the nematode C. elegans , which is able to take up protein-bound Moco from its diet and distribute it through its body until Moco reaches sulfite oxidase, where it becomes inserted into this essential enzyme [ 159 , 160 ]. Kurt discovered this phenomenon, and I contribute our biochemical knowledge to his project.…”
Section: Discussionmentioning
confidence: 99%
“…However, such Moco deficient mutants can still grow by feeding with bait microorganisms expressing Moco-dependent enzymes 15 or, more recently, by supplementing Moco-binding proteins. 16 Characterization of this Moco salvage pathway in C. elegans may provide hints to the future application to deliver Moco to human MoCD patients.…”
Section: Translating the Mechanistic And Structural Understanding To ...mentioning
confidence: 99%